2017
DOI: 10.1002/ijgo.12322
|View full text |Cite
|
Sign up to set email alerts
|

Prospective study of the effect of maternal body mass index on labor progress in nulliparous women in Egypt

Abstract: Patterns in labor progress, including cervical dilatation rate and labor duration, differed among patients with different BMI. ClinicalTrials.gov: NCT02686073.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 22 publications
(53 reference statements)
3
13
0
Order By: Relevance
“…However, in terms of CS implementation during the active period, there was a significant difference between pre-pregnant obese women and pre-pregnant women of normal weight. Maged and colleagues, [3] in a prospective study carried out in Egypt, discovered a different prevalence of cervical dilatation and duration of labor in pregnant women with different BMI values. Carlhalland co-workers demonstrated that, with a pre-pregnancy BMI >30 kg/m 2 , the probability of prolonged latency, active-phase stagnation, and prolonged active phase increased, whereas the duration of the second phase of labor was not significantly different from that of low and normal body weight group.…”
mentioning
confidence: 99%
“…However, in terms of CS implementation during the active period, there was a significant difference between pre-pregnant obese women and pre-pregnant women of normal weight. Maged and colleagues, [3] in a prospective study carried out in Egypt, discovered a different prevalence of cervical dilatation and duration of labor in pregnant women with different BMI values. Carlhalland co-workers demonstrated that, with a pre-pregnancy BMI >30 kg/m 2 , the probability of prolonged latency, active-phase stagnation, and prolonged active phase increased, whereas the duration of the second phase of labor was not significantly different from that of low and normal body weight group.…”
mentioning
confidence: 99%
“…The adverse effects of high BMI before pregnancy and excessive WGDP and delivery process have been investigated repeatedly. [4][5][6][7] Low or high BMI has adverse effects on pregnancy outcomes and infant's health. The risk of large-for-gestational-age births (LGA), cesarean delivery and childhood obesity are increased in overweight women (BMI 25.0-29.9 kg/m 2 ) and maternal obesity (BMI ≥30.0 kg/m 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, in a systematic review of the exiting evidence up to 2016, it was found that the cesarean childbirths were significantly higher among women with greater BMI values [13] . However, recent primary studies have reported contradicting findings [14][15][16][17] . In the present study, we analyzed the predictor role of the pre-pregnancy BMI on the risk of cesarean section in Peruvian women.…”
Section: Introductionmentioning
confidence: 94%
“…Existing evidence has shown that the maternal and fetal mortality and morbidity rates are greater among pregnant women with higher BMI values than in those with lower BMI figures. For example, pregnant women with overweight and obesity tended to have more prolonged gestational and delivery periods, instrumental deliveries, and macrosomic babies (Birthweight: >4000 gr) [12][13][14][15][16] . Yet, the association between BMI and the risk of delivery via cesarean is still unclear.…”
Section: Introductionmentioning
confidence: 99%